Building Bridges, Crossing Borders - Getty, Ann Darby (Book collections on Project MUSE., 2014)
"Kyler Daniels was born in 1988 with a profound bilateral hearing loss. Her deafness went undetected for a year since newborn screening for hearing loss was not yet available. Kyler benefited, however, from the great support of her family and a string of excellent professionals in deaf education, including Ann Darby Getty, the author of this shared, experiential story. As soon as they realized that their daughter was deaf, Kyler's parents, who were hearing, immediately began to learn sign language. They also engaged Darby, a parent/infant educator employed by the state school for the deaf, to work with Kyler. From the age of 13 months until Kyler's college graduation 22 years later, Darby was involved in her education and development. Despite living in a rural area, Kyler enjoyed an array of services, including parent/infant education, sign language interaction/modeling, speech and language therapy, and also a cochlear implant. At the same time that she developed her speech skills, sign language continued to be a critically important facet of her communication. In grade school, she learned with other deaf students, while in high school, she worked successfully in mainstream classrooms with interpreters and notetakers. As a college graduate, gifted artist, and veterinarian's assistant today, Kyler exemplifies how a balanced approach to deaf education, using all resources at hand, can achieve remarkable results. Her story serves as a model for parents of other deaf children and the professionals who work with them"--